Effect of Heating Rate on the Responses of LiF: Mg, Cu, Na, Si Thermoluminescent Phosphor - Ha, Vu Thi Thai; Hai, Nguyen Thi Quy; Long, Nguyen Ngoc (Communications in Physics, 2011)
In the current work the glow curves for LiF:Mg,Cu,Na,Si thermoluminescent material were measured and analyzed by using a function approximating to the well-known Randall-Wilkins first-order expression. The influence of different heating rates on thermoluminescent glow-peak maximum temperature, peak height and integrated area of the glow peak was investigated for LiF:Mg,Cu,Na,Si phosphor. The results show that the glow-peak temperature, peak height and glow peak area increase with increasing heating rate, while the full width at half maximum of glow peak almost keeps constant in the range of heating rates studied.